PENERAPAN DAN PEMBERIAN BANTUAN HUKUM BAGI MASYARAKAT KURANG MAMPU - Sunggara, Muhamad Adystia; Meliana, Yang; Gunawan, Arifin Faqih; Yuliana, Sri (Solusi, 2021)
The protection and recognition of human rights of every individual or citizen is an obligation for the state as a logical consequence of its establishment as a rule of law and a person has the right to be treated equally before the law, including for poor people who are in trouble with the law. This research is normative legal research or doctrinal legal research with a legal inventory approach, which collects norms that have been identified as legal norms. The conclusion of this study is that legal aid is not a guarantee in the form of access to law and justice for the poor because the application of legal aid at the practical level in the community still reaps several problems that hinder the realization of access to law and justice for the poor. First, the non-working normative legal framework. Second, the lack of legal awareness regarding legal aid. Third, access to justice which is formality. Fourth, discrimination and complicated procedures in funding legal aid. Fifth, there is no supervision in the application of legal aid.